ANDRAGOGI DALAM PEMBELAJARAN BAHASA ARAB - M. Hasyim (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
The objective of this study is to get empirical evidence whether there is a significant difference between the class which is taught by andragogy technique and which is taught by conventional technique. This article describes that technique is one of the important factors in conducting Arabic class. This study categorized as an experimental research. The data is collected by giving the test for both experimental and conventional class. The result of the study shows that experimental class which is taught by applying andragogy technique get higher score than the conventional one. Means that Al-Ittihad Islamic Boarding School get higher score than Ulil Albâb. It seems that technique influences the quality of teaching and learning Arabic.DOI: 10.15408/a.v2i1.1512